KETERAMPILAN PENGEMBANGAN MATERI PRAKTEK SPEAKING DALAM FORMAT DIALOG MAHASISWA S1 AGROTEKNOLOGI - Agung Budi Kurniawan (SINERGI : Jurnal Riset Ilmiah, 2026)
Developing speaking skills is a skill that must be mastered by non-English students. The researcher analyzed to what extend the implication of the students of S1 Agrotechnology of Universitas Tidar in developing the speaking materials in the dialogue format and its impact to their speaking perform. The subject of this research consists of 25 students who were divided into 12 dialogue groups in English class. The data was taken on 21 April 2026 when the subject were performing their middle-term test by applying an observation method. The first finding is that the students had prepared their material schema very well after getting the information about the midterm test schema. The second finding is the strengths, including increasing the multi-topic speaking material skill, and training the skill to work in a team. The next is giving mental readiness to students and their simulation. The negative impacts were also found, including the tendency to reminding their material preparation, some students forget some material, which makes them confused, needing a longer time for the preparation. The next finding is that the spontaneous material development gives an impact of giving stimulus of short thinking conditions to the student and giving nervousness to the students. The last finding is that the knowledge background of the students influences them perform to develop the speaking materials.